ChemInform Abstract: Inducamides A—C, Chlorinated Alkaloids from an RNA Polymerase Mutant Strain of Streptomyces sp. Issue 18 (May 2015) - Fu, Peng; Jamison, Matthew; La, Scott; MacMillan, John B.
Abstract Inducamide A (Ia), B (Ib) and C (II) are shown to not exhibit significant antibacterial activity, but (II) reveals modest cytotoxicity.